Dual diagnosis: unravelling the complexity of mitochondrial respiratory chain disorder and familial hypercholesterolemia in early childhood - Phadke, Abhishek K.; Kumble, Ali; Khan, Shuhadamol Arif; Raikar, Poonam S. (International Journal of Research in Medical Sciences, 2025)
Complex I deficiency is the most frequently encountered single mitochondrial enzyme deficiency in patients with a mitochondrial disorder. Most of patients present with symptoms similar to leukodystrophy. Pathogenic mutations identified in the majority of the 44 genes encoding the structural subunits of complex I. No cure for complex I deficiency and the treatment options restricted to symptomatic treatment. Here we report a case of mitochondrial complex I deficiency in an 11-month-old infant presented with failure to thrive, regression of milestones, and metabolic acidosis with a high anion gap and high lactate. MRI brain showed extensive white matter involvement. Before starting treatment with IEM cocktails, genetic testing was sent. Whole exome sequencing revealed homozygous variants in NDUFAF5 (Exon 6) associated with mitochondrial complex-I deficiency and heterozygous mutation in LDLR (+) familial hypercholesterolemia (FH) type 1. After starting treatment metabolic abnormalities got corrected. This rare co-occurrence highlights the importance of considering mitochondrial disorders in infants with unexplained metabolic acidosis and regression of milestones. The case emphasizes the need for early recognition and diagnosis to initiate appropriate management and genetic counselling. This unique combination of disorders expands our understanding of the genetic and phenotypic spectrum of mitochondrial diseases.